Spirituality-Based Psychotherapies in Relation to Social Media Addiction: A Review - Rupali Pundir; Shyam Lata Juyal (International Journal of Behavioral Sciences, 2024)
Social media addiction has become a pressing concern, characterized by compulsive usage that significantly impacts mental health. In the digital age, where the boundaries between the virtual and the real have blurred, social networking sites (SNS) have emerged as pivotal platforms that shape the lives of young people. Most people's life now revolve around social networking sites, particularly those of teens. Excessive engagement with social media can have adverse effects on individuals' minds, bodies, and spirits, potentially leading to dependence and addiction. Thus, an effective intervention would require addressing these domains which are mind, body and soul. While all the intervention available such as CBT or digital detox are effective in providing short term relief, they often overlook the existential and deeper aspects leading to addiction. Primary articles were searched using two databases namely PubMed and Google Scholar. Then other relevant articles were reviewed using the reference list of the primary studies. The present study explains how spirituality can provide a deeper sense of meaning, enhance emotional regulation, and promote resilience. Moving forward, the mechanism underlying the impact of spirituality-based interventions have been highlighted in this study and explains how just by shifting the focus from external validation to inner fulfilment, spirituality-based psychotherapy encourages individuals to find peace within the chaos of digital life. Lastly, the potential challenges that could be faced while planning and implementing the spirituality-based psychotherapies are discussed to complement the overall concept of the paper. Hence, integrating spiritual principles and practices is a key to transform the addictive patterns associated with social media.
Keywords: Addiction; Meditation; social media; social networking sites; spirituality